Fulfillment of The Rights and Obligations of The Prisoner's Husband at Class III Correctional Institutions Gunung Tua (Implementation of Marriage Law No.16 of 2019 Amendment to Law No. 1 Of 1974) - Mhd Yadi Harahap; Hafsah Hafsah; Tarmizi Amin Harahap (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
This research uses qualitative research or field research. Data was collected through interviews, observation, and documentation of the fulfillment of the obligations of husbands who are prisoners to their wives and children. Then it will be analyzed using descriptive analysis techniques, which is a method that describes and interprets data that has been collected in an inductive mindset. The results show that 50% of husbands who are prisoners cannot provide a living for their wives and children, and wives prefer to end their marriages. Meanwhile, another 50% choose to maintain the marriage, because the wife of the inmate can still earn a living with the results of the business she manages. Fulfillment of income is also obtained from the family, both the wife's family and the husband's family.